2014
DOI: 10.1139/gen-2014-0145
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of acetohydroxyacid synthase1 gene in chickpea conferring resistance to imazamox herbicide

Abstract: Chickpea (Cicer arietinum L.) production in the Canadian prairies is challenging due to a lack of effective weed management mainly because of poor competition ability of the crop and limited registered herbicide options. Chickpea genotype with resistance to imidazolinone (IMI) herbicides has been identified. A point mutation in the acetohydroxyacid synthase1 (AHAS1) gene at C581 to T581, resulting in an amino acid substitution from Ala194 to Val194 (position 205, standardized to arabidopsis), confers the resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…Moreover, ligand-protein contact analysis [44] suggested that the T203I substitution may result in a conformational change in the protein or dimer interface due to the presence of the larger hydrophobic I residue, thus modifying the herbicide-binding site (Figures 5 and 6). Similar results have been obtained with the A205V substitution [45][46][47].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, ligand-protein contact analysis [44] suggested that the T203I substitution may result in a conformational change in the protein or dimer interface due to the presence of the larger hydrophobic I residue, thus modifying the herbicide-binding site (Figures 5 and 6). Similar results have been obtained with the A205V substitution [45][46][47].…”
Section: Discussionsupporting
confidence: 87%
“…Replacement of the hydrophilic T203 by the larger hydrophobic I residue has a double effect: steric overlapping and hydrophobic-hydrophilic repulsion with R199, which is expected to strongly affect the IQ-binding pocket. Hydrophobic cluster analysis of the WT IMI-sensitive CH-AHAS1 and two mutants-IMI-resistant (T203V) CH-AHAS-M2033 (this work) and the A205V mutant [45,46]-showed that both IMI-resistant mutants change the hydrophobic clusters of the AHAS1 protein (Figure 6), altering their distribution, and leading to changes in the IMI-binding site.…”
Section: Mutation Changes Ahas1 Structurementioning
confidence: 63%
“…17,32,33 Although cross-resistance patterns have generally been associated with the position of the substitution in the AHAS gene, it has recently been observed that they can also be dependent on a range of factors including species, fitness of the plant and specific amino acid substitution. 19 In other species, such as chickpea and Arabidopsis, the Ala205Val AHAS substitution has been found to confer tolerance to imidazolinone herbicides, but not to the sulfonylurea herbicides, 34,35 whereas the same substitution conferred cross-tolerance across both imidazolinone and sulfonylurea herbicides in yeast. 17 In sunflower, the Ala205Val substitution has been found to confer a high level of tolerance to imidazolinone herbicides and partial tolerance to sulfonylurea herbicides, 36,37 which appears to be consistent with our observations in faba bean.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation was also confirmed in chickpea. qPCR analysis indicated that there is no significant change in transcription levels of chickpea AHAS1 between sensitive and tolerant genotypes after IMI herbicide application [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can inhibit the activity of AHAS through binding to a quinone-binding site. IMI herbicides are registered for use on non-pulse crops including rapeseed, sunflower, barley, spring wheat, oats, and pulse crops: lentil, dry bean, field pea and soybean [ 6 ].…”
Section: Introductionmentioning
confidence: 99%